ANALYSIS OF USING THE TARBIYATUL MU'ALLIMIN AL-ISLAMIYAH CURRICULUM: EFFECTIVENESS AND EFFICIENCY ON STUDENT LEARNING ACHIEVEMENTS - Muhammad Rizal Fadli; Bambang Sunatar; Hasbullah Hasbullah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to analyze the effectiveness and efficiency of implementing the Tarbiyyatul Muallimin Al-Islamiyah (TMI) curriculum in improving student achievement. The research used a quantitative descriptive approach with data collected through questionnaires, observations, curriculum document analysis, and interviews involving 31 alumni from the 2022–2024 intake. Data analysis was conducted using descriptive statistical testing with SPSS version 24. The results revealed that curriculum effectiveness had a positive and significant effect on student achievement, with a significance value of 0.021 (p < 0.05) and a t-count of 2.443 greater than the t-table value of 1.695. Curriculum efficiency also had a positive and significant influence, with a significance value of 0.000 (p < 0.05) and a t-count of 12.699, exceeding the t-table value. Furthermore, both curriculum effectiveness and efficiency jointly contributed 88.5% to the improvement of student learning achievement, indicating that the curriculum implementation plays a crucial role in academic success. The implications of this study highlight the importance of evaluating and controlling extracurricular programs—especially language activities—by teachers and staff of TMI Al-Ghuroba Modern Islamic Boarding School, Sorong Regency, to enhance the overall quality and effectiveness of learning activities.